Improvement of Analytical Methods for the Determination of Polyphenolic Bioactive Compounds in Berry Fruits - Marisa Carmela Caruso; Fernanda Galgano; Maria Pecora; Roberta Tolve; Maria Verrastro; Fabio Favati (Journal of Chemistry)
Berry fruits contain high levels of different phytochemicals, most of which are phenolic molecules. Fruits of the same cultivar from different locations and different harvest years have different chemical compositions, particularly related to polyphenols. The difference may be due to specific climatic conditions, the type of soil in which the plants grow, and the stresses to which the plants were subjected because these phytochemicals are produced as a defense mechanism through a secondary metabolic process. For this reason, it is important to establish simple and reliable procedure to determine polyphenolic compounds in berry fruits considering the increasing attention on these compounds for different potential uses. In order to choose and to improve the most adequate analytical procedure for the determination of the polyphenolic substances in berry fruits, different methods were applied and compared on samples of elderberry and blackberry.